THE EFFECT OF REALIA ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE PARAGRAPH - Karmila; Sumarsih (Universitas Negeri Medan, 2015)
This study was an attempt to discover the effect of using Realia on students’ achievement in writing descriptive paragraph. It was conducted by using experimental research design. The population of this research was the eight grade students of MTS S GUPPI Tanjung Harapan, Rantauprapat which consists of three parallel classes with the total number of students are 90. The sample of this research was taken by random sampling. The result was class VIII-A consisting 30 students became the experimental group and VIII-B consisting of 30 students became the control group. The experimental group was taught by using Realia meanwhile the control group was taught by using Picture. The instrument for collecting the data was writing test. In the calculation of Ttest, the mean of students’ score in experimental group was 21.8 and the mean of students’ score in control group was 14.6. Standard deviation of experimental group was 1630.2, standard deviation of control group was 1568.8, and the total number of samples was 58, Tobserved is higher than Ttable. 3.977 > 2.004 at the level significance 0.05 for two tailed. The finding is if hypothesis stated that there is significant effect of using Realia as media learning on students’ achievement in writing descriptive paragraph is accepted.